Trade in information technology goods: Adapting the ITA to 21st century technological change - Iana Dreyer; Brian Hindley (European Centre for International Political Economy (ECIPE), 2008)
Trade in technology goods has increased rapidly. The twelve-year-old Information Technology Agreement (ITA) in the WTO has facilitated this process and has contributed to the dissemination of technology across the world. Yet the ITA needs to be improved to provide for further trade liberalization of ICT (information and communications technology) goods. The ITA has weaknesses that must be addressed if the ITA is to maintain its relevance. A fundamental problem in the ITA is its product coverage, in particular its exclusion of key consumer electronic products, which was largely at the insistence of the EU. In an era of technological "convergence" among ICT products, this exclusion has the potential to progressively erode ITA coverage. A further problem is that the ITA is based on a rigid positive listing of products that poses problems with multifunctional goods. These matters form the background of a current dispute in the WTO. Furthermore, the ITA imposes no discipline on non-tariff barriers to ICT trade. The mechanisms the Agreement put in place to expand coverage have failed, and this paper proposes new negotiations leading to a better-designed ITA, to start after the dispute in the WTO is settled. These should guarantee a balance of interests involving at least the EU, the US, Japan, and China. A new "grand bargain" will entail a movement to free trade in consumer electronics "paid for" by redutions in non-tariff barriers to trade in ICT goods.
Keywords: F13; F14; F53; O14; O24; 330; World Trade Organization; Information Technology Agreement; trade in information technology; customs classification; dispute settlement